Rechallenge of denosumab in advanced giant cell tumor of the bone after atypical femur fracture: A case report and review of literature - Vincenzo Nasca; Anna Maria Frezza; Carlo Morosi; Ciriaco Buonomenna; Antonina Parafioriti; Giorgio Zappalà; Federica Bini; Paolo Giovanni Casali; Paolo Giovanni Casali; Mattia Loppini; Mattia Loppini; Silvia Stacchiotti (Frontiers in Oncology, 2022)
Giant cell tumor of the bone (GCTB) is a locally aggressive neoplasm where surgery is often curative. However, it can rarely give rise to distant metastases. Currently, the only available active therapeutic option for unresectable GCTB is denosumab, an anti-RANKL monoclonal antibody that dampens the aggressive osteolysis typically seen in this disease. For advanced/metastatic GCTB, denosumab should be continued lifelong, and although it is usually well tolerated, important questions may arise about the long-term safety of this drug. In fact, uncommon but severe toxicities can occur and eventually lead to denosumab discontinuation, such as atypical fracture of the femur (AFF). The optimal management of treatment-related AFF is a matter of debate, and to date, it is unknown whether reintroduction of denosumab at disease progression is a clinically feasible option, as no reports have been provided so far. Hereinafter, we present a case of a patient with metastatic GCTB who suffered from AFF after several years of denosumab; we describe the clinical features, orthopedic treatment, and oncological outcomes, finally providing the first evidence that denosumab rechallenge after AFF occurrence may be a safe and viable option at GCTB progression.